PENGARUH GAYA HIDUP, CITRA MEREK DAN ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN HIJAB ZOYA (STUDI PADA STORE ZOYA, MALL PEKANBARU) - Rosnani "; Okta Karneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine how much influence lifestyle, brand image and product attributes on the purchasing decision of the hijab zo. The sample in this study was taken as many as 100 respondents and the technique used was Pusposive Sampling. The data in this study used a survey method through questionnaires filled by consumers. Data obtained using simple regression analysis and multiple regression analysis. The results of this study indicate that lifestyle has a effect on purchasing decisions. Brand image has a effect on purchasing decisions. Product attributes affect purchasing decisions. And simultaneously lifestyle, brand image and product attributes have a effect on purchasing decisions. Further research is recommended to use other methods in examining purchasing decisions, for example through in-depth interviews with respondents. Keywords: Lifestyle, Brand Image, Product Attributes, and Purchasing                      Decisions